Extending the treatment options in alcohol dependence: a randomized controlled study of as-needed nalmefene - Mann, Karl (Biological psychiatry, 2013)
Background: There is a large treatment gap in alcohol dependence, and current treatments are only moderately effective in preventing relapse. New treatment modalities, allowing for reduction of alcohol consumption as a treatment goal are needed. This study evaluated the efficacy of as-needed use of the opioid system modulator nalmefene in reducing alcohol consumption in patients with alcohol dependence. Methods: Six hundred and four patients (placebo = 298; nalmefene = 306),≥18 years of age, with a diagnosis of alcohol dependence,≥6 heavy drinking days, and average alcohol consumption≥World Health Organization medium drinking risk level in the 4 weeks preceding screening, were randomized (1:1) to 24 weeks of as-needed placebo or nalmefene 18 mg. Results: Patients taking placebo (n = 289) and patients taking nalmefene (n = 290) were included in the efficacy analyses. At Month 6, there was a significant effect of nalmefene compared with placebo in reducing the number of heavy drinking days (−2.3 days [95% confidence interval:−3.8 to−.8]; p = .0021) and total alcohol consumption (−11.0 g/day [95% confidence interval:−16.8 to−5.1]; p = .0003). Improvements in Clinical Global Impression and liver enzymes were larger in the nalmefene group compared with placebo at Week 24. Adverse events (most mild or moderate) and dropouts due to adverse events were more common with nalmefene than placebo. The number of patients with serious adverse events was similar in the two groups. Conclusions: Nalmefene provides clinical benefit, constitutes a potential new pharmacological treatment paradigm in terms of the treatment goal and dosing regimen, and provides a method to address the unmet medical need in patients with alcohol dependence that need to reduce their alcohol consumption.